Impact of microannulus on the efficiency of heat transfer in the bottomhole - Santos, Livio; Dahi Taleghani, Arash (Frontiers in Energy Research, 2023)
To ensure feasible power generation from closed-loop geothermal wells, deeper wells are required to reach higher temperature zones. However, weak bonding between cement and casing or cement and formation may allow formation of a small gap (known as microannulus), which could have a negative effect on the heat extraction rate and consequently compromises the entire investment. Previous projects have reported that the output temperatures were significantly lower than the expected values, and the cause is believed to be cement debonding. This study aims to develop a reliable simulation model to demonstrate the impact of microannulus in closed-loop geothermal systems. Multi-physics finite element analysis is used to construct models with and without microannulus. The microannulus is modeled based on real cement evaluation logs, with gaps varying between a few micrometers to few millimeters. In extreme cases, the presence of microannulus is found to decrease the geothermal power by more than 35%. Furthermore, the possibility of heat loss containment is investigated by a sensitivity study of wellbore parameters. These sensitivity analyses demonstrate that cement and geothermal fluids with higher thermal conductivity can improve but cannot compensate the presence of microannuli. The results also highlight the importance of proper cementing design to ensure wellbore integrity and avoid geothermal power loss.